Answer:
y = -3
Step-by-step explanation:
9x + 7y = -12
Let x = 1
9 (1) + 7y = -12
9 + 7y = -12
Subtract 9 from each side
9 -9 + 7y = -12-9
7y = -21
Divide each side by 7
7y/7 = -21/7
y = -3
Answer:
y = -3
Step-by-step explanation:
9x + 7y = -12
9(1) + 7y = -12
9 + 7y = -12
7y = -12 - 9
7y = -21 (divide both sides by 7)
y = -3
Answer:
b
Step-by-step explanation:
-2
-6
-23
-26
Answer:
Step-by-step explanation:
A. 18 + 30 (use the associative property)
B. 41 + 7 (use order of operations)
C. 30 + 25 (use the commutative property)
D. 25 + 30 (use the distributive property)